Factors affecting financial literacy of accounting students - Abdul Latiff, Mohd Zakwan; Abd Rahman, Nurulhuda; Hashim, Marshita (UiTM Cawangan Johor, 2024)
Over the last few decades, tertiary education students have been adversely affected by the high cost of living. Most students need help keeping up with their living standards due to their limited financial literacy knowledge. This situation has resulted in them being burdened with debt and being on the brink of bankruptcy. This study aimed to examine the impact of age, financial socialisation, and specific motivation on the financial literacy of accounting students. The research scope focused on factors influencing financial literacy, including knowledge, attitude, and behaviour. This study involved accounting students from all levels at UiTM Faculty of Accountancy in the Shah Alam and Puncak Alam campuses. The findings revealed that financial knowledge and behaviour were positively and significantly associated with financial literacy. Moreover, financial motivation had a positive and significant impact on financial literacy among UiTM accounting students. This study contributes to the existing literature on financial literacy and will aid society, academics, and policymakers in focusing on key elements necessary to improve students 'financial literacy.